Exploring the Influence of Word of Mouth, Brand Image, and Social Media Marketing on Yamaha Motorcycle Purchase Intention in Denpasar City - Ni Komang Tri Puspaningrum; Ni Putu Nita Anggraini; I Wayan Gede Anton Setiawan Jodi; Putu Oktaviani; Ni Putu Mutiara Kasih (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The motorcycle industry in Indonesia has experienced rapid development, particularly in the scooter segment, which dominates the market due to its convenience and efficiency. Despite this growth, Yamaha’s market share has shown fluctuations, indicating inconsistent consumer purchase intention. This study aims to analyze the effect of Word of Mouth (WOM), Brand Image, and Social Media Marketing (SMM) on purchase intention of Yamaha motorcycles in Denpasar City, using the Theory of Reasoned Action (TRA) as the underlying framework. The research employed a quantitative approach with a survey method involving 104 respondents. Data were analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results demonstrate that WOM, Brand Image, and SMM each have a positive and significant effect on purchase intention, with WOM emerging as the most dominant factor. The regression model indicates that these three variables jointly explain 77.2% of the variance in purchase intention, while the remaining 22.8% is explained by other factors not included in this study. The findings confirm that strengthening WOM, enhancing brand image, and optimizing social media strategies are essential to increase consumer purchase intention. This study contributes to both theoretical development and managerial practice in the field of consumer behavior and marketing strategy in the automotive industry.